The Salvador/Warts/Hippo pathway controls regenerative tissue growth in Drosophila melanogaster. - Grusche, F.A.; Degoutin, J.L.; Richardson, H.E.; Harvey, K.F. (Developmental Biology, 2011)
During tissue regeneration, cell proliferation replaces missing structures to restore organ function. Regenerative potential differs greatly between organs and organisms; for example some amphibians can regrow entire limbs whereas mammals cannot. The process of regeneration relies on several signaling pathways that control developmental tissue growth, and implies the existence of organ size-control checkpoints that regulate both developmental, and regenerative, growth. Here we explore the role of one such checkpoint, the Salvador-Warts-Hippo pathway, in tissue regeneration. The Salvador-Warts-Hippo pathway limits tissue growth by repressing the Yorkie transcriptional co-activator. Several proteins serve as upstream modulators of this pathway including the atypical cadherins, Dachsous and Fat, whilst the atypical myosin, Dachs, functions downstream of Fat to activate Yorkie. Using Drosophila melanogaster imaginal discs we show that Salvador-Warts-Hippo pathway activity is repressed in regenerating tissue and that Yorkie is rate-limiting for regeneration of the developing wing. We show that regeneration is compromised in dachs mutant wing discs, but that proteins in addition to Fat and Dachs are likely to modulate Yorkie activity in regenerating cells. In conclusion our data reveal the importance of Yorkie hyperactivation for tissue regeneration and suggest that multiple upstream inputs, including Fat-Dachsous signaling, sense tissue damage and regulate Yorkie activity during regeneration of epithelial tissues.